Optimalisasi Limbah Organik menjadi Pupuk Cair di Gampong Pasie Aceh Baro - Evi Julianita Harahap; Kasmawati Kasmawati; Rahmah Husna Yana; Nhyra Kamala Putri; Suci Eka Putri (Universitas Pahlawan Tuanku Tambusai, 2026)
Household organic waste in Gampong Pasie Aceh Baro has not been optimally utilized, potentially increasing the environmental burden and community dependence on chemical fertilizers. This community service initiative focuses on enhancing the knowledge and skills of the Women Farmers Group,